2008
DOI: 10.2466/pr0.102.2.532-538
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Demands of Error Processing

Abstract: This study used a dual-task methodology to assess attention demands associated with error processing during an anticipation-timing task. A difference was predicted in attention demands during feedback on trials with correct responses and errors. This was addressed by requiring participants to respond to a probe reaction-time stimulus after augmented feedback presentation. 16 participants (8 men, 8 women) completed two phases, the reaction time task only and the anticipation-timing task with the probe RT task. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 11 publications
(11 reference statements)
1
16
0
Order By: Relevance
“…The findings of the study are partially consistent with those of Koehn et al (2008), which highlighted an association between error processing and increased cognitive demand. Koehn et al found that PRT, in the time period immediately following presentation of augmented feedback, was lengthened when feedback indicated an error, relative to when feedback indicated no error.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The findings of the study are partially consistent with those of Koehn et al (2008), which highlighted an association between error processing and increased cognitive demand. Koehn et al found that PRT, in the time period immediately following presentation of augmented feedback, was lengthened when feedback indicated an error, relative to when feedback indicated no error.…”
Section: Discussionsupporting
confidence: 88%
“…Increased cognitive activity probably represented evaluation of the magnitude and cause of the error and possibly methods of correcting the error on subsequent trials. However, the cognitive system for processing spatial error (current study) may be somewhat different for processing temporal error (Koehn et al, 2008). For example, it may be more difficult to identify or consciously monitor very small discrepancies in anticipation timing than to identify and monitor the spatial parameters of whole body movements.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To account for these findings, providing KR based on relatively good trials has been speculated to increase the motivation of the participant to learn the task, that as a result, reinforces the cognitive processes required to reproduce the correct motor response on upcoming trials and subsequent learning (Badami, VaezMousavi, Wulf, & Namazizadeh, 2011;Chiviacowsky & Wulf, 2007;. In fact, the cognitive demands required to reproduce a correct response have proven to be less demanding and perhaps more desirable for the learner compared to the cognitive demands associated with correcting an error (Chiviacowsky & Wulf, 2002, 2005Kohen, Dickinson, & Goodman, 2008).…”
Section: Introductionmentioning
confidence: 94%
“…The preference for feedback after good trials has been interpreted as a motivational factor during skill acquisition (Chiviacowsky & Wulf, 2002) and the perception that less cognitive effort is required to reproduce a successful response compared to the cognitive effort required to update a motor plan for an unsuccessful response (Chiviacowsky & Wulf, 2002, 2005Koehen, Dickinson, & Goodman, 2008). The benefits of self-control have been primarily demonstrated in younger adults (see Wulf, 2007 for a review) and more recently in 10 year old children (Chiviacowsky, Wulf, Laroque de Medeiros, Kaefer, & Tani, 2008).…”
Section: Introductionmentioning
confidence: 98%